2012
DOI: 10.1094/cchem-03-12-0029-r
|View full text |Cite
|
Sign up to set email alerts
|

Tibetan Hull‐less Barley (Hordeum vulgare L.) as a Potential Source of Antioxidants

Abstract: Tibetan hull‐less barley grows at above 4,000 m altitude. One variety grown in the plain and three varieties grown in Tibet were collected from Tianjin and Lhasa. The barleys were polished into five fractions. Total soluble phenolic content (TSPC), total antioxidant capacity (TAC), and their correlation were investigated. Phenolic compounds were analyzed by HPLC, and TSPC content was evaluated by the Folin–Ciocalteu colorimetric method. TAC was measured using 2,2‐diphenyl‐1‐picrylhydrazyl, 2,2′‐azinobis‐(3‐eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
1
22
0
2
Order By: Relevance
“…TPC did not show a very significant correlation (p<0.05) with growing altitude of the cultivars. Gong et al (2012) reported similar levels of total phenolic content in Tibetan hulless barley. Total flavonoid content (TFC) of whole barley flour varied significantly (p<0.05) within cultivars (Table 3) …”
Section: Tpc Tfc and Mcamentioning
confidence: 79%
“…TPC did not show a very significant correlation (p<0.05) with growing altitude of the cultivars. Gong et al (2012) reported similar levels of total phenolic content in Tibetan hulless barley. Total flavonoid content (TFC) of whole barley flour varied significantly (p<0.05) within cultivars (Table 3) …”
Section: Tpc Tfc and Mcamentioning
confidence: 79%
“…The antioxidant compound profile, including phenolics and flavonoids, of Qingke has been partly examined, and studies have suggested that this cultivar possesses a unique antioxidant compound profile with potential health benefits and ability to mitigate oxidative stress (Du, Zhu, & Xu, ; Gong, Jin, Wu, Wu, & Zhang, ; Liu et al, ; Zhu et al, ). However, limited information is available about the antioxidant potential of Qingke.…”
Section: Introductionmentioning
confidence: 99%
“…Lahouar et al () showed that whole grain barley has an anticarcinogenic effect on azoxymethane‐induced colon carcinogenesis in rats. However, in contrast to other whole grains, previous investigations on highland barley mainly focus on highland barley bran extracts (Gong, Jin, Wu, Wu, & Zhang, ) and the changes in their anthocyanins during seed maturation and after harvest (Kohyama, Ono, & Yanagisawa, ). Few studies have reported the phytochemical profiles and antioxidant activities of highland barley.…”
Section: Introductionmentioning
confidence: 99%